2017
DOI: 10.1016/j.bbrep.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The influence of retinoic acid on the human oligodendrocyte precursor cells by RNA-sequencing

Abstract: Retinoic acid (RA), a metabolite of vitamin A, has been found to influence regeneration in the adult central nervous system (CNS). There may be an effect of RA in the recovery/repair in multiple sclerosis (MS), an autoimmune and neurodegenerative disease of the CNS. We hypothesized that RA is a regulator of the further differentiation of oligodendrocyte precursor cells (OPCs) – cells key to the remyelination process in MS. We conducted studies utilizing RNA-sequencing in human embryonic stem cell (hESC)-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…RARα has been shown to be constitutively present in OPCs and to be transiently increased by RA (Laeng et al, 1994), probably RARα2, because only this isoform has been reported to be induced by RA (Leroy et al, 1991), whereas RARβ is not constitutively expressed in OPCs (Laeng et al, 1994). However, prolonged treatment of human-derived OPCs with RA results in RARβ upregulation and in the upregulation of two known transcriptional inhibitors of oligodendrocyte differentiation, Hes5 and Id4 (Kim et al, 2017). In embryonic SC, where relatively high levels of retinoids are present, RA was found to inhibit oligodendrocyte differentiation during early embryonic development, permitting OPCs dispersal throughout the entire SC (Noll and Miller, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…RARα has been shown to be constitutively present in OPCs and to be transiently increased by RA (Laeng et al, 1994), probably RARα2, because only this isoform has been reported to be induced by RA (Leroy et al, 1991), whereas RARβ is not constitutively expressed in OPCs (Laeng et al, 1994). However, prolonged treatment of human-derived OPCs with RA results in RARβ upregulation and in the upregulation of two known transcriptional inhibitors of oligodendrocyte differentiation, Hes5 and Id4 (Kim et al, 2017). In embryonic SC, where relatively high levels of retinoids are present, RA was found to inhibit oligodendrocyte differentiation during early embryonic development, permitting OPCs dispersal throughout the entire SC (Noll and Miller, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The 2 most highly differentially expressed proteins (mhDEPs, with log 2 fold-change ≥ 5) on d20, MDK and RBP1, truly reflect the role of this leading step, the pre-OPC stage, in OL generation. Both mhDEPs instigate pre-OPC specification toward OL differentiation [ 114–117 ]. Among the 22 DEPs at the pre-OPC stage (Fig.…”
Section: Data Descriptionmentioning
confidence: 99%
“…S5 ). The correlation of this differential repatterning with the high abundance of known pre-OPC proteins such as MDK, RBP1 [ 114–117 ], SOX3 [ 118 ], and TNFRSF10B [ 119 ] points to the potential of these d20 DEPS to be used as biomarkers for the pre-OPC state.…”
Section: Data Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oli-neuM express Myrf [8,19,52]; thus, we concentrated our attention on nuclear factors acting downstream of Myrf expression. Of these, the 9-cis retinoic acid-responsive element RXRγ is known to be upregulated at the transition from NPCs to the OPC lineage [53], as well as at lesions in the lysolecithin-induced murine demyelination model [54]. Furthermore, we have previously shown that the RXRγ inhibitor UV3003 downregulates MBP expression upon Clobetasol or Halcinonide treatment of Oli-neuM [8].…”
Section: Resultsmentioning
confidence: 99%